Litter N-content influences soil millipede abundance, species richness and feeding preferences in a semi-evergreen dry forest of Guadeloupe (Lesser Antilles) - Loranger-Merciris, G; Imbert, D; Bernhard-Reversat, F.; Lavelle, Patrick M.; Ponge, JF (Springer, 2008)
Despite the impact of soil millipedes on litter fragmentation in tropical forests, there have been few studies dealing with factors determining their habitat preference in these ecosystems. In a natural secondary dry forest of Guadeloupe on Leptosol, two complementary studies were carried out in order to test the hypothesis that litter N-content strongly influences millipede distribution. Millipede abundance and species richness were described in the field under two tree species, Bursera simaruba and Pisonia subcordata, and were related to the chemical characteristics of their foliage. In addition, a laboratory experiment was done in order to assess millipede feeding preferences regarding the chemical characteristics of leaves from various species. Millipede abundance and species richness were significantly higher under P. subcordata than under B. simaruba, probably due to the higher N content of P. subcordata leaves. Moreover, millipedes fed preferentially on N-rich leaves. The present study confirms that there was a close correlation between the preferred food, its chemical composition and the local distribution of millipede populations.